2022
DOI: 10.1101/2022.01.10.475524
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex-specific regulation of metabolic health and vertebrate lifespan by AMP biosynthesis

Abstract: The loss of energy homeostasis seen during aging, is causally linked to multiple age-related pathologies. The AMP-activated protein kinase (AMPK) directly senses cellular energy levels, which are reflected in the ratio between AMP:ATP. However, the genetic regulation of vertebrate aging by the AMPK pathway remains poorly understood. Here, we manipulate ATP production by mutating APRT, a key enzyme in AMP biosynthesis, and extend vertebrate lifespan in a male-specific manner. Using a multi-omics approach, we de… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 166 publications
(261 reference statements)
0
13
0
Order By: Relevance
“…This could indicate that AMPK γ2 function is physiologically required exclusively upon fasting and explain why, unlike AMPK γ1 , chronic activation of AMPK γ2 leads to metabolic dysfunctions in normally fed mice or humans 45,46 . Astre et al showed that mutation in the APRT gene, a key enzyme in AMP biosynthesis, mimics a caloric-restriction effect, inducing lifespan extension in killifish males 47 . This effect was associated with higher expression of the γ2 subunit, possibly indicating that higher activation of AMPK γ2 is beneficial under energetic stress conditions and implies that various dietary interventions might represent a concrete strategy to counter the pathological effect of AMPK γ2 hyperactivity in humans.…”
Section: Discussionmentioning
confidence: 99%
“…This could indicate that AMPK γ2 function is physiologically required exclusively upon fasting and explain why, unlike AMPK γ1 , chronic activation of AMPK γ2 leads to metabolic dysfunctions in normally fed mice or humans 45,46 . Astre et al showed that mutation in the APRT gene, a key enzyme in AMP biosynthesis, mimics a caloric-restriction effect, inducing lifespan extension in killifish males 47 . This effect was associated with higher expression of the γ2 subunit, possibly indicating that higher activation of AMPK γ2 is beneficial under energetic stress conditions and implies that various dietary interventions might represent a concrete strategy to counter the pathological effect of AMPK γ2 hyperactivity in humans.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently demonstrated that the killifish model could be used to identify novel regulators of aging, which involve systemic modulation of metabolism 14 . Therefore, beyond our current application, it would be exciting to expand this platform to investigate systemic factors as modifiers of health and disease.…”
Section: Discussionmentioning
confidence: 99%
“…Tissues samples were processed as described previously [12][13][14][15][48][49][50][51][52][53][54][55][56][57][58][59] . Briefly, fish were euthanized with 500 mg/l tricaine (MS222, #A5040, Sigma).…”
Section: Hematoxylin and Eosinmentioning
confidence: 99%
See 1 more Smart Citation
“…Tools to advance genetic interrogation of the killifish have been developed, including a sequenced genome (Reichwald et al, 2015; Valenzano et al, 2015) and Tol2 transgenesis (Allard et al, 2013; Hartmann and Englert, 2012; Valenzano et al, 2011), as well as CRISPR/Cas9-mediated knock-out (Harel et al, 2015) and CRISPR/Cas13-mediated knock-down (Kushawah et al, 2020). This genetic toolkit has enabled discoveries about the mechanisms of aging (Astre et al, 2022a; Bradshaw et al, 2022; Chen et al, 2022; Harel et al, 2022; Louka et al, 2022; Matsui et al, 2019; Smith et al, 2017; Van Houcke et al, 2021b), regeneration (Vanhunsel et al, 2022a; Vanhunsel et al, 2021; Vanhunsel et al, 2022b; Wang et al, 2020), evolution (Cui et al, 2019; Sahm et al, 2017; Singh et al, 2021; Willemsen et al, 2020), development (Abitua et al, 2021; Dolfi et al, 2019), and ‘suspended animation’ (Hu et al, 2020; Singh et al, 2021).…”
Section: Main Textmentioning
confidence: 99%